Human Orc2 localizes to centrosomes, centromeres and heterochromatin during chromosome inheritance - Prasanth, Supriya G (2005)
Correction to: The EMBO Journal (2004) 23, 2651–2663. doi:10.1038/sj.emboj.7600255